Mechanics of fluids - Merle C. Potter (Brooks Cole /Thompson Learning, 2002)
MECHANICS OF FLUIDS presents fluid mechanics so that students gain an understanding of and an ability to analyze the important phenomena encountered by practicing engineers. The authors succeed in this through the use of several pedagogical tools (Margin Notes, Chapter Outlines, Summaries, and a nomenclature list) that help students visualize the many difficult-to-understand phenomena of fluid mechanics. Potter and Wiggert base their explanations on basic physical concepts and mathematics which are accessible to undergraduate engineering students, such as differential equations and vector algebra